Avaliação da presença de bisfenol A, seus análogos e outros plastificantes em café em cápsulas - Júlia Célia Lima Gomes (2024)
Plasticizers are substances added to plastic materials to increase their flexibility and plasticity. In this study, the migration of bisphenol A and other plasticizers into capsule coffees was evaluated using liquid chromatography coupled with high-resolution mass spectrometry. Sample preparation was carried out using acetonitrile as the extraction solvent and salting-out partitioning. The instrumental conditions used in the analyses were determined based on the analytical standard of bisphenol A, aiming for its identification at the level of the specific migration limit set by legislation (0.05 mg L-1). The method also sought to broadly assess the potential presence of other compounds, including bisphenol A analogs and other types of plasticizers in general. After analyzing the capsule coffee samples (11 types of capsule coffees, 1 type of coffee bean, and 5 coffee maker machines) in duplicate, it was found that the presence of bisphenol A and its analogs was not significant, as their signal intensity was consistent with levels below those established by the Brazilian legislation. On the other hand, various other plasticizers, including phthalates, acrylates, epoxides, and organic acids, were detected. Comparing coffees prepared from different types of capsules, plasticizers were detected even in aluminum and compostable paper capsules. This result gives rise to several possible hypotheses: (i) even capsules made from other materials may have some coating containing plasticizers; (ii) other parts of the coffee makers themselves, made of plastic, could lead to the migration of plasticizers into the beverage; or (iii) the coffee itself might already have some contamination with plasticizers, originating from its processing before being packed in the capsules. Principal component analysis allowed for examining similarities between coffees prepared from capsules made with different materials.